2021
DOI: 10.1186/s13041-021-00773-y
|View full text |Cite
|
Sign up to set email alerts
|

Projection-dependent heterogeneity of cerebellar granule cell calcium responses

Abstract: Cerebellar granule cells (GCs) relay mossy fiber (MF) inputs to Purkinje cell dendrites via their axons, the parallel fibers (PFs), which are individually located at a given sublayer of the molecular layer (ML). Although a certain degree of heterogeneity among GCs has been recently reported, variability of GC responses to MF inputs has never been associated with their most notable structural variability, location of their projecting PFs in the ML. Here, we utilize an adeno-associated virus (AAV)-mediated label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Another study found that neighboring GC somas in the GCL labeled with calcium indicator gave rise to sparsely distributed PFs 10 . Our previous results obtained by using the AAV-GABRα6 were consistent with these studies, in terms that there is no association in the anterior-posterior axis between positions of GC somas in the GCL and PF locations in the ML 12 . In addition, our present study demonstrated random distributions of GC somas also in the dorsal-ventral or lateral axis, regardless of their bundled PFs.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Another study found that neighboring GC somas in the GCL labeled with calcium indicator gave rise to sparsely distributed PFs 10 . Our previous results obtained by using the AAV-GABRα6 were consistent with these studies, in terms that there is no association in the anterior-posterior axis between positions of GC somas in the GCL and PF locations in the ML 12 . In addition, our present study demonstrated random distributions of GC somas also in the dorsal-ventral or lateral axis, regardless of their bundled PFs.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study suggested the differences in GC electrophysiological properties according to their PF locations, based on the correlation between PF locations and GC soma locations that was suggested using sparse GC labeling 8 . However, other studies 9 11 , including our previous study 12 , demonstrated that there is no apparent correlation between GC soma locations and their PF locations along the anterior-posterior axis. Thus, such association between synaptic organizations from MFs to GCs in the GCL and sublayers of PF projections remained under debate.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations